Correlation Between Training and Education of Human Resources and Business Performance of Small and Medium Enterprises - Klepić, Iva (Naše gospodarstvo/Our economy, 2021)
Human resources (HR) represent a crucial resource of enterprises. This especially applies to small and medium-sized enterprises (SMEs), in which HR can create a competitive advantage and affect survival and development. Changes in the business environment, the need for new knowledge, skills and abilities due to changes in the market and business all lead to widening the gap between existing and required competencies of employees. In the process of training and education of HR, employees acquire the necessary knowledge, refine their skills and/or acquire new skills, and experience. More to the point, they obtain the competencies they need to stay and/or become successful in their job and future jobs that they will perform in the enterprise. The principal aim of this research is to determine the correlation between training and education of HR and business performance of SMEs. The survey was conducted in SMEs in the Federation of B&H from August to September 2020. An original questionnaire was created for the research, used for collecting the views on the HR training and education of top managers as well as four business performance perspectives of companies based on the Balanced Scorecard model. Data were analysed using SPSS 20.0. The following were used from the statistical procedures: Pearson’s coefficient of correlation, t-test for independent samples, Spearman’s correlation of coefficient and Mann-Whitney U test (depending on the results distribution). The results of the survey showed that there is a correlation between training and education of HR and business performance in SMEs. In addition, the survey results indicated differences among the enterprises in terms of their size; i.e., between small and medium-sized enterprises. However, those differences are not statistically significant.